Palmerston : a biography - Brown, David, 1972- (Yale University Press, 2010)
A grand and fascinating figure in Victorian politics, the charismatic Lord Palmerston (1784-1865) served as foreign secretary for fifteen years and prime minister for nine, engaged in struggles with everyone from the Duke of Wellington to Lord John Russell to Queen Victoria and Prince Albert, engineered the emergence of Britain as a dominant great power, and played a major role in the development of liberalism and the Liberal Party. This comprehensive biography, informed by unprecedented research in the statesman's personal archives, gives full weight not only to Palmerston's foreign policy achievements, but also to his domestic political activity, political thought, life as a landlord, and private life and affairs. Through the lens of the milieu of his times, the book pinpoints for the first time the nature and extent of Palmerston's contributions to the making of modern Britain. - Publisher.